Dampak Keberadaan Pasar Modern terhadap Pendapatan Pedagang Pasar Tradisional (Studi Kasus Pedagang Pasar Sentral Pangkep Kabupaten Pangkajene Kepulauan) - Nurlinda; Marhawati; Tuti Supatminingsih; Rahmatullah; Syamsu Rijal (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
This study aims to determine the impact of the existence of a modern market on the income of traditional market traders in Indonesia Pasar Sentral Pangkep Kabupaten Pangkajene Kepulauan. This study uses qualitative research with an interactive approach and data collection techniques using observation, interviews and documentation techniques which are then analyzed. Based on the results of interviews obtained, the results of this study show that the existence of modern markets is close together pasar sentral pangkep have an influence on the income of traders in pasar sentral pangkep Kabupaten Pangkajene dan Kepulauan. The presence of modern markets can have an impact on the income of traditional market traders, namely reducing their income, especially traders of mixed goods, bags and clothes, shoes/sandals. The decrease in income by 49% is due to the decrease in consumers in traditional markets who prefer modern markets with the facilities and infrastructure offered by modern markets that can make consumers more comfortable and safe, the prices offered are relatively cheap with high quality goods. Buyers also sometimes get discounts that can attract buyers.